2020
DOI: 10.7554/elife.50458
|View full text |Cite
|
Sign up to set email alerts
|

TLR5 participates in the TLR4 receptor complex and promotes MyD88-dependent signaling in environmental lung injury

Abstract: Lung disease causes significant morbidity and mortality, and is exacerbated by environmental injury, for example through lipopolysaccharide (LPS) or ozone (O3). Toll-like receptors (TLRs) orchestrate immune responses to injury by recognizing pathogen- or danger-associated molecular patterns. TLR4, the prototypic receptor for LPS, also mediates inflammation after O3, triggered by endogenous hyaluronan. Regulation of TLR4 signaling is incompletely understood. TLR5, the flagellin receptor, is expressed in alveola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 48 publications
3
42
0
Order By: Relevance
“…Hussain et al recently demonstrated that the flagella receptor TLR5 is physically associated with the LPS receptor TLR4, diverting TLR4 signalling to the MyD88 pathway. After exposure of primary murine macrophages to ultra-pure LPS, TLR5 was co-immunopreserved with MyD88, TLR4 and LPS, suggesting an updated paradigm for TLR4/TLR5 signalling [64].…”
Section: Host Immune Response Against P Aeruginosamentioning
confidence: 99%
“…Hussain et al recently demonstrated that the flagella receptor TLR5 is physically associated with the LPS receptor TLR4, diverting TLR4 signalling to the MyD88 pathway. After exposure of primary murine macrophages to ultra-pure LPS, TLR5 was co-immunopreserved with MyD88, TLR4 and LPS, suggesting an updated paradigm for TLR4/TLR5 signalling [64].…”
Section: Host Immune Response Against P Aeruginosamentioning
confidence: 99%
“…Interestingly, the release of MIP-2 from microglia exposed to LPS was significantly enhanced in the absence of TLR5, while IL-6 and IL-10 responses were reduced compared to wild-type cells. One may speculate that TLR5 cooperates with TLR4 [28], which is the LPS-recognizing receptor, in an unknown manner, resulting in enhancing (IL-6, IL-10) or inhibiting (MIP-2) effects on cytokine production. In addition, as TLR5 can interact with TIR-domain-containing adapter-inducing interferon-β (TRIF), LPS stimulation might modulate the cytokine response through the associated pathway [8].…”
Section: Discussionmentioning
confidence: 99%
“…FlgC is the structural unit of the bacterial agellum, which can interact with TLR5-expressing cells (e.g., monocytes, neutrophils, DCs, lymphocytes, and macrophages) as an agonist of TLR5 51,52 . Some studies reported the synergistic effects of the TLR4 and 5 signaling pathways; therefore, the use of FlgC might modulate initial innate and then the subsequent adaptive immune responses 51,53 . We have validated the interaction of vaccine construct with the TLR4 and TLR5 using molecular docking and then molecular dynamics simulations (Figs.…”
Section: Discussionmentioning
confidence: 99%